Lagrangian Model Framework: A Cutting Edge towards Predicting Pollutants Transport in River Benue of Greater City Yola, Nigeria - Burmamu, B.R.; Law, P.L. (SJIF, 2015)
The purpose of this paper is to predict the fate and transport behaviour of pollutants discharged into the Benue River through point and non point sources using Lagrangian equations of fluid motion in MATLAB default environment. To achieve this, water samples were collected from the source of this river at Adamaoua Mountains of Cameroon and Yola, the study area in well preconditioned plastic bottles and analysed for the presence of heavy metals in the river. Findings of this study showed that only Zn, Cu, and Mn concentration levels were below the permissible limits of water quality standards while Fe, Cd, Cr, Ni, and Co values were by far above the threshold limits. The model predicted output indicated a one-dimensional non uniform linear graph of pollutants’ movement due to advective forces and water current effects with average water velocity of 0.66m/s covering a travel distance of 1500 meters within 15 minutes.